2022
DOI: 10.1155/2022/5937802
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Classes of Antihypertensive Drugs on Patients with COVID-19 and Hypertension: A Mini-Review

Abstract: Hypertension is a major risk factor for cardiovascular disease. Previous studies showed that patients with hypertension are at an increased risk of developing severe COVID-19 infection. Therefore, proper blood pressure control in hypertensive patients with COVID-19 is of great importance. In this review, we discussed the effects of different classes of antihypertensive drugs on patients with hypertension and COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…No association was found between using other antihypertensive drugs including CCBs, beta‐blockers, and diuretics and the incidence and severity of COVID‐19. In contrast to other reviews, Nozari and Hamidizadeh investigated the effects of antihypertensive drugs on COVID‐19 only in patients with essential hypertension 17 . They suggest that ACE inhibitors and ARBs may be better choices to treat hypertension in this population.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…No association was found between using other antihypertensive drugs including CCBs, beta‐blockers, and diuretics and the incidence and severity of COVID‐19. In contrast to other reviews, Nozari and Hamidizadeh investigated the effects of antihypertensive drugs on COVID‐19 only in patients with essential hypertension 17 . They suggest that ACE inhibitors and ARBs may be better choices to treat hypertension in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that ACE inhibitors were the drugs with the highest likelihood of being initiated to a patient infected with COVID‐19 is not surprising since according to some hypotheses, it may have some benefit compared with the other antihypertensive agents. 16 , 17 In a meta‐analysis, Ren et al concluded that the mortality and severity of COVID‐19 were significantly lower in patients taking ACE inhibitors/ARBs than in controls. 16 No association was found between using other antihypertensive drugs including CCBs, beta‐blockers, and diuretics and the incidence and severity of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations